Melatonin: Current Status and Future Perspectives in Plant Science - Nawaz, Muhammad A.; Huang, Yuan; Bie, Zhilong; Ahmed, Waqar; Reiter, Russel J.; Niu, Mengliang; Hameed, Saba (Frontiers in Plant Science, 2016)
Melatonin (N-acetyl-5-methoxytryptamine) is a ubiquitous molecule with pleiotropic actions in different organisms. It performs many important functions in human, animals and plants; these range from regulating circadian rhythms in animals to controlling senescence in plants. In this review, we summarize the available information regarding the presence of melatonin in different plant species, along with highlighting its biosynthesis and mechanisms of action. We also collected the available information on the effects of melatonin application on commercially important crops to improve their growth and development. Additionally, we have identified many new aspects where melatonin may have possible roles in plants, for example, its function in improving the storage life and quality of fruits and vegetables, its role in vascular reconnection during the grafting process and nutrient uptake from roots by modifying root architecture. Another potentially important aspect is the production of melatonin-rich food crops (cereals, fruits and vegetables) through combination of conventional and modern breeding approaches, to increase plant resistance against biotic and abiotic stress, leading to improved crop yields and the nutraceutical value of produce to solve food security issues.